The influence of personal factors on adolescents’ physical and mental health: from the perspective of sports commitment - Yulin Yang; Yansen Li; Jing Yu, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
The purpose of this study is to examine the determinants of teenagers’ physical and mental health via the lens of sports commitment. The survey of 1000 senior high school students revealed that adolescents’ stress tolerance varied by gender and grade. Teenagers’ physical activity levels, frequency, and duration are largely consistent and reasonable. Physical activity has a major effect on adolescents’ stress resistance, mental health, and interpersonal relationships. Through statistical analysis of 930 teenagers, it was determined that 533 people engaged in low physical activity, accounting for 57.4 per cent of the total population. 242 people engaged in moderate physical activity, accounting for 26.1 per cent of the population. 155 people engaged in vigorous physical activity, accounting for 16.5 per cent of the total population. According to statistical analysis of the basic amount of physical activity performed by teenagers, teenagers’ amount of physical activity is relatively concentrated between low and moderate levels of physical activity, indicating that teenagers’ overall level of physical activity remains stable. Commitment to sports may fully mobilise social support, increase teens’ happiness via numerous channels, foster a positive learning and training environment, and bolster supervision and positive psychology cultivation.